A região grave do espectro sonoro: aspectos teóricos e práticos na produção musical - Fernando Braga Campos (2013)
This is a practical theoretical work about the necessary knowledge that an audio professional should have to capture and manipulate sounds that reach the low end of the spectrum, more specifically, those that concentrate most of its energy on the three first octaves of the audible range (20Hz to 160Hz). Focused on the professional praxis of music production, information from a myriad of fields as acoustics, electrics and cognitive psychology were gathered and related to the subject. Surveys and interviews were realized with audio professional as to give to their empirical knowledge a main role on the structural basis of the text. As results we have got a profile of Belo Horizonte's audio professionals, their perspectives and a collection of what they state as being important experiences to their audio education.